2008
DOI: 10.2143/ac.63.5.2033225
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart disease in children with Down’s syndrome: Turkish experience of 13 years

Abstract: This is the first study concerning the frequency and type of CHD observed in Turkish children with DS. The high frequency of AVSD in Turkish children with DS implied that early screening for CHDs by echocardiography is crucial. The correction of AVSDs in paediatric patients with DS should be performed in the first 6 months of life to avoid irreversible haemodynamic consequences of the defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
30
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 15 publications
7
30
2
3
Order By: Relevance
“…Cardiol., 8 (1): 20-26, 2015 No ) found that approximately 50% of Down syndrome children in Libya had CHD which is near to Malayza (Azman et al, 2007). On the other hand, the frequency of CHD in Down syndrome observed in this study is less than that reported in Oman (60%) (Venugopalan and Agarwal, 2003), Turkey (78%) (Nisli et al, 2008) and Guatimala (80%) (Vida et al, 2005). In comparison to local studies done in Saudi Arabia, Al-Jarallah (2009) reported that CHD was diagnosed in 49% of Down syndrome children in Riyadh region, the capital of Saudi Arabia.…”
Section: Discussioncontrasting
confidence: 70%
“…Cardiol., 8 (1): 20-26, 2015 No ) found that approximately 50% of Down syndrome children in Libya had CHD which is near to Malayza (Azman et al, 2007). On the other hand, the frequency of CHD in Down syndrome observed in this study is less than that reported in Oman (60%) (Venugopalan and Agarwal, 2003), Turkey (78%) (Nisli et al, 2008) and Guatimala (80%) (Vida et al, 2005). In comparison to local studies done in Saudi Arabia, Al-Jarallah (2009) reported that CHD was diagnosed in 49% of Down syndrome children in Riyadh region, the capital of Saudi Arabia.…”
Section: Discussioncontrasting
confidence: 70%
“…8 A large number of chromosomal abnormalities such as trisomy 21, 18,and 13 are associated with CHD in 5-8% cases. 9,10 Because of improvement in health care system, more patients are surviving and entering into adulthood. At the same time diagnosis in neonatal period also increased because of awareness among neonatologist about the disease.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7][8][9][10][11][12][13][14][15][16][17] The types of heart defect may vary according to geographic region. In this study, the most common type was atrial septal defect, which was similar to the findings from other Table 1.…”
Section: Discussionmentioning
confidence: 99%